S-nitrosylation of Src by NR2B-nNOS signal causes Src activation and NR2B tyrosine phosphorylation in levodopa-induced dyskinetic rat model. (March 2019) - Ba, M; Ding, W; Guan, L; Lv, Y; Kong, M
Abnormality in Src PSD-95 NR2B signaling complex assemble occurs in levodopa-induced dyskinesia (LID). N -methyl-D-aspartate receptor (NMDAR) subunit NR2B tyrosine phosphorylation mediated by Src family protein tyrosine kinases is closely associated with dyskinesia. Src autophosphorylation (p-Src) is an important part of Src-catalyzed phosphorylation of NR2B. In addition, the neuronal nitric oxide synthase (nNOS)-derived NO (nNOS/NO) signal which was also involved in dyskinesia recently was proved to participate in the regulation of Src function. Yet, the detailed signal mechanism about the interactions of NR2B, nNOS, and Src is still unknown. In the present study, we investigated the influences of nNOS on Src activation and NR2B tyrosine phosphorylation in dyskinetic rat model by immunoblotting and immunoprecipitation. The results demonstrated that chronic levodopa treatment resulted in downregulation of p-nNOS-S847, one marker of nNOS overactivation. Coinstantaneously, the S-nitrosylation (SNO-Src) and autophosphorylation (p-Src) of Src and NR2B tyrosine phosphorylation were upregulated in dyskinetic rat model. Conversely, administration of 7-NI, one nNOS inhibitor, reversed all these effects of levodopa treatment. Besides, NR2B-containing NMDAR (NR2B/NMDAR) antagonist CP-101, 606 could upregulate p-nNOS-S847 and thus attenuate nNOS activation and simultaneously reduce the SNO-Src, p-Src, and NR2B tyrosine phosphorylation. Taken together, the S-nitrosylation of Src is caused by nNOS/NO signal, which is overactivated via Ca 2+ influx dependent on NR2B/NMDAR, and subsequently facilitates Src auto-tyrosine phosphorylation and further phosphorylates NR2B. The "NR2B/NMDAR–nNOS/NO–SNO-Src–p-Src–NR2B/NMDAR" signaling cycle may be the molecular basis of NR2B tyrosine phosphorylation upward positive feedback, which demonstrates the possibility as one latent target for dyskinesia therapy.